The Impact of Offline and Online Advertising on Consumer Purchase Behavior - Lykhnenko, Oleg; Král, Petr, 1979-; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The main goal of this bachelor’s thesis is to find out which types of ads, offline or online, have a greater impact on consumer purchase behavior. The first two chapters of the thesis show the theoretical basis of buying behavior discussing traditional and newly created consumer paths to purchase, as well as the influence that offline and online advertising have on consumer purchase behavior. The research in the final third chapter was realized employing the quantitative method of data collection - online questionnaire, that was distributed by the author via different social media platforms. With the sample size of 112 participants, the research yielded valuable results on the impact of traditional and digital adverts on consumer purchase behavior based on the four stages purchasing funnel - AIDA. The author of the thesis believes that the findings will be useful for marketing professionals to identify influential types of advertising and hence favorably allocate marketing budgets.
Vedoucí práce: Petr Král
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses